Kepastian Hukum Terhadap Perjanjian Pembiayaan Didahului SKMHT Tanpa APHT - Victoria Damanik, Jessica Bintang; Badriyah, Siti Malikhatun (Fakultas Syariah INSURI Ponorogo, 2023)
Ownership of land rights is an interest for Indonesian that is used for various purposes, one of which is as collateral in a financing agreement. The advantage of being a collateral object is to have a stable value and tend to increase. The purpose of this study is to analyze the legal protection of creditors who experience problems when knowing debtor defaults and their position of creditors who only have SKMHT without APHT due to notary negligence. This research method is qualitative with a normative juridical research type. The results of the research are protection for SKMHT holders enforced despite the negligence of the Notary/PPAT. In addition, the recommendation that the PPAT/Notary should have SKMHT management to avoid legal problems when debtor defaults.